2015
DOI: 10.11646/zootaxa.3937.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the genus Pseudopomatias and its relatives (Gastropoda: Cyclophoroidea: Pupinidae)

Abstract: The present paper revises all species that have been assigned to Pseudopomatias Möllendorff, 1885 and Nodopomatias Gude, 1921. The following new species are described: Pseudopomatias abletti Páll-Gergely, n. sp. (northeastern India), Pseudopomatias harli Páll-Gergely, n. sp. (northeastern India), Pseudopomatias linanprietoae Páll-Gergely n. sp. (Laos), Pseudopomatias maasseni Páll-Gergely & Hunyadi, n. sp. (Vietnam and China), Pseudopomatias nitens Páll-Gergely n. sp. (Vietnam), Pseudopomatias prestoni Páll-Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 32 publications
1
18
0
3
Order By: Relevance
“…Bole and Velkovrh (1986) mentioned only one subterranean species from South Asia that was recorded in Sri Lanka (Srilankiella horanae Bole & Velkovrh, 1986, nomen nudum according Kabat and Hershler 1993) and 12 probable pomatiopsid taxa from Japan belonging to the genera Akiyoshia Kuroda & Habe, 1954, Cochliopopsis Mori, 1938 and Moria Kuroda & Habe, 1958. Despite the recent increased interest in South and East Asian terrestrial micromolluscs (Maassen 2008, Culver 2012, Páll-Gergely 2014, Páll-Gergely et al 2015, Inkhavilay et al 2016, Páll-Gergely et al 2016, Páll-Gergely et al 2017, our knowledge of the stygobiont gastropod fauna of the region has not advanced significantly since 1986. Despite the extraordinary high radiation of surface freshwater Pomatiopsidae Bourguignat, 1863, species of the tribe Triculini Annandale, 1924 in the Mekong tributary (Deshayes and Jullien 1876;Crosse and Fischer 1879;Annandale 1919;Brandt 1968Brandt , 1970Brandt , 1974Davis 1979, Temcharoen 1971Brandt and Temcharoen 1974;Strong et al 2007), the troglobiont and stygobiont species of the area remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Bole and Velkovrh (1986) mentioned only one subterranean species from South Asia that was recorded in Sri Lanka (Srilankiella horanae Bole & Velkovrh, 1986, nomen nudum according Kabat and Hershler 1993) and 12 probable pomatiopsid taxa from Japan belonging to the genera Akiyoshia Kuroda & Habe, 1954, Cochliopopsis Mori, 1938 and Moria Kuroda & Habe, 1958. Despite the recent increased interest in South and East Asian terrestrial micromolluscs (Maassen 2008, Culver 2012, Páll-Gergely 2014, Páll-Gergely et al 2015, Inkhavilay et al 2016, Páll-Gergely et al 2016, Páll-Gergely et al 2017, our knowledge of the stygobiont gastropod fauna of the region has not advanced significantly since 1986. Despite the extraordinary high radiation of surface freshwater Pomatiopsidae Bourguignat, 1863, species of the tribe Triculini Annandale, 1924 in the Mekong tributary (Deshayes and Jullien 1876;Crosse and Fischer 1879;Annandale 1919;Brandt 1968Brandt , 1970Brandt , 1974Davis 1979, Temcharoen 1971Brandt and Temcharoen 1974;Strong et al 2007), the troglobiont and stygobiont species of the area remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“… Pseudopomatias sophiae Páll-Gergely in Páll-Gergely et al 2015a: 41, figs 6b, 9f. Type locality: Tonkin, Trinh-Thuong [Bat Xat District, Lao Cai Province, Vietnam].…”
Section: Resultsmentioning
confidence: 99%
“…No material of this species was found, and only the type specimens were examined. Páll-Gergely et al (2015a) described this species based on Saurin’s specimens identified as “ Pseudopomatias fulvus .” For the current interpretation of Pa Hia, see Páll-Gergely et al (2016: 13).…”
Section: Resultsmentioning
confidence: 99%
“…However, the exact locality could not be determined (Nordsieck 2002, Páll-Gergely 2014, Páll-Gergely 2015c). A geological report (Marutani 2006), mentioned the name “Ban Namthong” in brackets after “Pa Hia”.…”
Section: Taxonomic Descriptionsmentioning
confidence: 99%